Ice Hockey Lung – A Case of Mass Nitrogen Dioxide Poisoning in The Czech Republic - Kristian Brat; Zdenek Merta; Marek Plutinsky; Jana Skrickova; Miroslav Stanek Ing (Canadian Respiratory Journal, 2013)
Nitrogen dioxide (NO2) is a toxic gas, a product of combustion in malfunctioning ice-resurfacing machines. NO2 poisoning is rare but potentially lethal. The authors report a case of mass NO2 poisoning involving 15 amateur ice hockey players in the Czech Republic. All players were treated in the Department of Respiratory Diseases at Brno University Hospital in November 2010 – three as inpatients because they developed pneumonitis. All patients were followed-up until November 2011. Complete recovery in all but one patient was achieved by December 2010. None of the 15 patients developed asthma-like disease or chronic cough. Corticosteroids appeared to be useful in treatment. Electric-powered ice-resurfacing machines are preferable in indoor ice skating arenas.